Socio-economic burden of COVID-19 in the Russian Federation - A. S. Kolbin; D. Yu. Belousov; Yu. M. Gomon; Yu. E. Balykina; I. G. Ivanov (Izdatelstvo OKI, 2020)
Purpose. Assessment of the socio-economic burden of COVID-19 in the Russian Federation (RF). Materials and methods. Identification and assessment of direct medical, direct non-medical costs, as well as indirect costs associated with the development of the coronavirus infection epidemic. When calculating the socio-economic burden, the prevalence-based calculation approach was chosen. The sources of data on the epidemiology of the disease were data from the Ministry of Health and data from the Government of the Russian Federation. Results. The socio-economic burden of COVID-19 in the Russian Federation will amount to 4.6 trillion rubles ($71.1 billion) or 4 % from GDP. In the cost structure, more than half of the costs are direct non-medical expenses (58.62 %), indirect expenses due to GDP losses are 40.65 %, direct medical expenses are only less than 1 % (0.74 %). The results of the sensitivity analysis showed that the extension of the self-isolation period from 1 month to 1.5 and 2 months will lead to an increase in the share of indirect expenses from 40.65 % (1 month) to 56.08 (1.5 months) and 67.76 % (2 months) for all expenses in connection with the COVID-19 epidemic. At the same time, the socio-economic burden of COVID-19 will amount to 6.2 and 8.5 trillion rubles, respectively. Conclusions. The epidemic of a novel coronavirus infection will lead to great economic losses in the Russian society.